Insulators for 2D nanoelectronics: the gap to bridge - Yury Yu. Illarionov (Nature Portfolio, 2020)
The lack of scalable, high-quality insulators is a major problem hindering the progress on electronic devices built from 2D materials. Here, the authors review the current state-of-the-art and the future prospects of suitable insulators for 2D technologies.